Grounding Critical Communication Studies - Fuchs, Christian (International communication. Four-Volume Set. Volume 2)

New Marxian Times! Reflections on the 4th ICTs and Society Conference "Critique, Democracy and Philosophy in 21st Century Information Society. Towards Critical Theories of Social Media" - Fuchs, Christian (tripleC - Journal for a Global Sustainable Information Society)

Report on Theoretical Frameworks and Previous Empirical Research. Deliverable D1.1 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Amicelle, Anthony; Bus, Jacques; El-Baba, Taghrid; Fuchs, Christian; Mordini, Emilio; Rebera, Andrew; Robinson, Neil; Trottier, Daniel; Venier, Silvia; Wright, Steve

Societal Impact Report. Deliverable D1.4 of the EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action” (grant agreement number: 285635) - Mordini, Emilio; Bus, Jacques; Rebera, Andrew P.; Venier, Silvia; McCarthy, Sadhbh; Hayes, Ben; Wright, Steve; Deering, Daniel; Fuchs, Christian; Trottier, Daniel; Krieglsteiner, Susann; El-Baba, Taghrid

NO2 Sensors with Reduced Power Consumption Based on Mesoporous Indium Oxide - Donato, Nicola; Wagner, Thorsten; Tiemann, Michael; Waitz, Thomas; Kohl, Claus-Dieter; Latino, Mariangela; Neri, Giovanni; Spadaro, Donatella; Malagù, Cesare (Lecture Notes in Electrical Engineering)
We report on sensing properties of ordered mesoporous nanostructures of In2O3 synthesized by nanocasting procedure towards NO2. The nanostructured material shows improved recover times and higher responses compared to non nanostructured material at low operating temperatures (100–150°C) thus allowing the use for low power NO2 sensors. These properties may be related to fast oxygen in and out propagation facilitated by an enhanced surface accessibility of the nanostructure.

Research Design & Data Analysis, Presentation, and Interpretation: Part One - Allmer, Thomas

Towards a Critical Theory of Surveillance in Informational Capitalism - Allmer, Thomas

Collective Effects in Second-Harmonic Generation from Split-Ring-Resonator Arrays - Linden, S.; Niesler, F. B. P.; Förstner, Jens; Grynko, Yevgen; Meier, Torsten; Wegener, M. (Physical Review Letters)
Optical experiments on second-harmonic generation from split-ring-resonator square arrays show a nonmonotonic dependence of the conversion efficiency on the lattice constant. This finding is interpreted in terms of a competition between dilution effects and linewidth or near-field changes due to interactions among the individual elements in the array.
Keywords: tet_topic_shg; tet_topic_meta

Weltliche deutsche Lieder in Messvertonungen des 15. und 16. Jahrhunderts. Eine erste Annäherung an das Repertoire - Höink, Dominik (Polyphone Messen im 15. und 16. Jahrhundert. Funktion, Kontext, Symbol)

Excitonic Eigenstates of Disordered Semiconductor Quantum Wires: Adaptive Wavelet Computation of Eigenvalues for the Electron-Hole Schrödinger Equation - Meier, Torsten; Mollet, Christian; Kunoth, Angela (Communications in Computational Physics)
A novel adaptive approach to compute the eigenenergies and eigenfunctions of the two-particle (electron-hole) Schrödinger equation including Coulomb attraction is presented. As an example, we analyze the energetically lowest exciton state of a thin one-dimensional semiconductor quantum wire in the presence of disorder which arises from the non-smooth interface between the wire and surrounding material. The eigenvalues of the corresponding Schrödinger equation, i.e., the one-dimensional exciton Wannier equation with disorder, correspond to the energies of excitons in the quantum wire. The wavefunctions, in turn, provide information on the optical properties of the wire. We reformulate the problem of two interacting particles that both can move in one dimension as a stationary eigenvalue problem with two spacial dimensions in an appropriate weak form whose bilinear form is arranged to be symmetric, continuous, and coercive. The disorder of the wire is modelled by adding a potential in the Hamiltonian which is generated by normally distributed random numbers. The numerical solution of this problem is based on adaptive wavelets. Our scheme allows for a convergence proof of the resulting scheme together with complexity estimates. Numerical examples demonstrate the behavior of the smallest eigenvalue, the ground state energies of the exciton, together with the eigenstates depending on the strength and spatial correlation of disorder.

Freiheit Macht Spaß. Zur Gouvernementaliät des Vergnügens - Hälterlein, Jens (Die vergnügte Gesellschaft. Ernsthafte Perspektiven auf modernes Amüsement)

Die Kritik der Konsumgesellschaft und die Praxis des Konsums - Hälterlein, Jens (Transnationale Vergesellschaftung. Verhandlungen des 35. Kongresses der Deutschen Gesellschaft für Soziologie in Frankfurt am Main 2010)

A normal form for definite quadratic forms over $\mathbb{F}_{q}[t]$ - Kirschmer, Markus (Mathematics of Computation)
An efficient algorithm to compute automorphism groups and isometries of definite Fq[t]-lattices for odd q is presented. The algorithm requires several square root computations in Fq₂ but no enumeration of orbits having more than eight elements.
Keywords: Applied Mathematics; Computational Mathematics; Algebra and Number Theory

Kirchentage, Festivals, Conventions - Religiöse Happenings als Orte der Glaubensbildung - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Kirchentags, Festivals, Conventions - Religious Happenings as Places for the Formation of Faith - Schroeter-Wittke, Harald (Glaubensbildung. Die Weitergabe des Glaubens im europäischen Protestantismus. Formaton of Faith. Handing down Faith in European Protestantism)

Chronikbücher - ein religionspädagogischer Kommentar in der Bibel - Schroeter-Wittke, Harald (Religionspädagogischer Kommentar zur Bibel)

Auf die Plätze - Sorgen - Los. Bibelarbeit auf dem Wege zu Mt 6,19-34 (BAB_093_0140) - Schroeter-Wittke, Harald; Keuchen, Marion; Leutzsch, Martin; Weßler, Sarah-Luise (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Muss die Freiheit wohl grenzenlos sein? Statement beim Feierabendmahl "Freiheit aufgetischt" am Zwinger (FRE_002_0181) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 33. DEKT Dresden 2011)

Religion als Thema der Unterhaltung im populären Spielfilm - Schroeter-Wittke, Harald (Handbuch Theologie und Populärer Film Band 3)

Liebe und Sexualität - Schroeter-Wittke, Harald (Evangelischer Taschenkatechismus)

Religionspädagogischer Kommentar zur Bibel

Ingolf U. Dalferth / Stefan Berg (Hg.): Gestalteter Klang - gestalteter Sinn. Orientierungsstrategien in Musik und Religion im Wandel der Zeit, Leipzig 2011 - Schroeter-Wittke, Harald (Theologische Revue)

Transmission und Eventuelle Kirche. Beobachtungen zu Kirchen-, Katholiken- und Weltjugendtagen zwischen Religion und Gesellschaft - Schroeter-Wittke, Harald (Zeitschrift für Theologie und Gemeinde)

Christoph Stange: Zum Umgang mit Religiöser Musik aus musikpädagogischer Sicht, Essen 2011 - Schroeter-Wittke, Harald (Theologische Literaturzeitung)

Schwebende Verfahren. Zur performativen Dimension der Seelsorge - Schroeter-Wittke, Harald (Wege zum Menschen)

If on a Winter's Night... Stings Weihnachtswahrnehmungen - Schroeter-Wittke, Harald (Praktische Theologie)

Presshärten von Rohren und Profilen mittels formlos festen Stoffen - Tekkaya, A. Erman; Mennecart, Thomas; Witulski, Jörg; Homberg, Werner; Rostek, Tim

Introduction: Marx is Back – The Importance of Marxist Theory and Research for Critical Communication Studies Today - Fuchs, Christian; Mosco, Vincent (tripleC – Open Access Journal for a Global Sustainable Information Society)

Towards Marxian Internet Studies - Fuchs, Christian (tripleC – Open Access Journal for a Global Sustainable Information Society)

Google Capitalism - Fuchs, Christian (tripleC – Journal for a Global Sustainable Information Society)

The Political Economy of Privacy on Facebook - Fuchs, Christian (Television & New Media)

Social Networking Sites and Complex Technology Assessment - Fuchs, Christian (E-Politics and Organizational Implications of the Internet: Power, Influence, and Social Change)

Una contribución la crítica de la economía política del capitalismo informacional transnacional - Fuchs, Christian (Nómadas)

Introduction: Internet and Surveillance - Fuchs, Christian; Boersma, Kees; Albrechtslund, Anders; Sandoval, Marisol (Internet and Surveillance. The Challenges of Web 2.0 and Social Media)

Critique of the Political Economy of Web 2.0 Surveillance - Fuchs, Christian (Internet and Surveillance. The Challenges of Web 2.0 and Social Media)

Gesellschaftskritik und Gesellschaftstheorie im Zeitalter des Internets - Fuchs, Christian (Kybernetik, evolutionäre Systemtheorie und Dialektik)

Media, War and Information Technology - Fuchs, Christian (Media & Terrorism. Global Perspectives)

Web 2.0 Surveillance and Art - Fuchs, Christian (Net Works: Case Studies in Web Art and Design)

Some Reflections on Manuel Castells’ Book “Networks of Outrage and Hope. Social Movements in the Internet Age“ - Fuchs, Christian (tripleC - Open Access Journal for a Global Sustainable Information Society)

With or Without Marx? With or Without Capitalism? A Rejoinder to Adam Arvidsson and Eleanor Colleoni - Fuchs, Christian (tripleC - Open Access Journal for a Global Sustainable Information Society)

Conference Report: The 4th ICTs and Society Conference: Critique, Democracy and Philosophy in 21st Century Information Society - Fuchs, Christian (Nordicom Information)

Why social media research matters for Occupy - Fuchs, Christian (Occupy News Network)

Implications of Deep Packet Inspection (DPI) Internet Surveillance for Society. The Privacy & Security-Research Paper Series, edited by Emilio Mordini and Christian Fuchs. Research Paper Number 1. EU FP7 project “PACT – Public Perception of Security and Privacy: Assessing Knowledge, Collecting Evidence, Translating Research into Action“ - Fuchs, Christian

Photoreduction of Mesoporous In2O3: Mechanistic Model and Utility in Gas Sensing - Wagner, Thorsten; Kohl, Claus-Dieter; Morandi, Sara; Malagù, Cesare; Donato, Nicola; Latino, Mariangela; Neri, Giovanni; Tiemann, Michael (Chemistry - A European Journal)
A model is proposed for the drop in electronic resistance of n-type semiconducting indium oxide (In2O3) upon illumination with light (350 nm, 3.5 eV) as well as for the (light-enhanced) sensitivity of In2O3 to oxidizing gases. Essential features of the model are photoreduction and a rate-limiting oxygen-diffusion step. Ordered, mesoporous In2O3 with a high specific surface area serves as a versatile system for experimental studies. Analytical techniques comprise conductivity measurements under a controlled atmosphere (synthetic air, pure N2) and temperature-resolved in-situ Fourier transform infrared (FTIR) spectroscopy. IR measurements reveal that oxygen vacancies form a donor level 0.18 eV below the conduction band.

Mesoporöse Silica - Moderne Funktionsmaterialien im Chemieunterricht - Wilke, Timm; Haffer, Stefanie; Tiemann, Michael; Waitz, Thomas (CHEMKON)
Poröse Funktionsmaterialien wie halbleitende Metalloxide, Kohlenstoff-Formen oder auch Silica werden aktuell von verschiedenen Wissenschaftsdisziplinen intensiv für Bereiche der Energiespeicherung, Sensorik, Katalyse und Stofftrennung erforscht. Im Beitrag werden schwerpunktmäßig geordnet-mesoporöse Silica-Materialien behandelt, die seit etwa 20 Jahren synthetisch zugänglich sind. Neben den Grundlagen der Herstellung über ein Templat-Verfahren werden im Beitrag auch drei Experimente vorgestellt, die im Chemieunterricht oder Schülerlabor durchgeführt werden können. Zudem wird gezeigt, dass sich verschiedene Aspekte aus dem Kompetenzbereich Fachwissen mit Hilfe des Themas „Mesoporöse Silica“ miteinander vernetzen lassen.

Mesoporous Al2O3 by Nanocasting: Relationship between Crystallinity and Mesoscopic Order - Haffer, Stefanie; Weinberger, Christian; Tiemann, Michael (European Journal of Inorganic Chemistry)
Crystalline, mesoporous alumina (Al2O3) materials with specific surface areas up to 400 m2 g–1 have been synthesized by means of structure replication (nanocasting) using CMK-8 carbon as a structure matrix. A crucial step during this synthesis procedure is the conversion of aluminum nitrate into aluminum hydroxide by treatment with ammonia vapor. The impact of this step was investigated in some detail. Prolonged vapor treatment has a positive impact on the crystallinity of the final Al2O3 products but at the same time leads to loss of mesoscopic structural order and porosity.

Mythisierungen in Vergangenheit und Gegenwart; Dirndl, Diva oder deutsches Mädel in Uniform?; Uniformierung und Uniformherstellung - Kraft, Kerstin

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Surface tension and its role for vertical wet etching of silicon - Brockmeier, A; Rodriguez, F J Santos; Harrison, M; Hilleringmann, Ulrich (Journal of Micromechanics and Microengineering)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; Electronic; Optical and Magnetic Materials

Mikrosystemtechnik auf Silizium - Hilleringmann, Ulrich